Measuring the Economic Risk of Covid-19 - Ilan Noy; Nguyen Doan; Benno Ferrarini; Donghyun Park (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We measure the economic risk of Covid-19 at a geo-spatially detailed resolution. In addition to data about the current prevalence of confirmed cases, we use data from 2014-2018 and a conceptual disaster risk model to compute measures for exposure, vulnerability, and resilience of the local economy to the shock of the epidemic. Using a battery of proxies for these four concepts, we calculate the hazard, the principal components of exposure and vulnerability to it, and of the economy's resilience (i.e., its ability of the recover rapidly from the shock). We find that the economic risk of this pandemic is particularly high in most of Sub-Saharan Africa, South Asia, and Southeast Asia. These results are consistent when comparing an ad-hoc equal weighting algorithm for the four components of the index, an algorithm that assumes equal hazard for all countries, and one based on estimated weights using previous aggregated Disability-Adjusted Life Years losses associated with communicable diseases.
Keywords: I10; 330; epidemic; Covid-19; risk measurement; economic impact